2023
DOI: 10.3390/min13050690
|View full text |Cite
|
Sign up to set email alerts
|

Study the Mechanical Properties of Geopolymer under Different Curing Conditions

Jinliang Liu,
Xiaohui Shi,
Guanhua Zhang
et al.

Abstract: The geopolymer is an environmentally friendly and high-performance material. Nowadays, how to improve the degree of the geopolymer’s reaction and enhance its mechanical properties has become a hot topic. This study used orthogonal tests to design the precursor mixing ratio, considering GGBS content (A), water/binder ratio (B), and alkaline activator modulus (C). The fly ash (FA) ground granulated blast furnace slag (GGBS)-based geopolymers were cured under two standard curing conditions: 40 °C under water and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Figure 12 shows the results of the XRD measurements conducted on the raw FAs and paste powder from each mixture cured in ambient conditions for one day. The main crystal phases present in the FA37 sample were anatase (hereinafter, A), periclase (hereinafter, P), quartz (hereinafter, Q), gehlenite (hereinafter, G), and hatrurite (hereinafter, H), while those in the FA21 sample were A, Q, G, and P, and these were analyzed based on the findings of previous studies [44][45][46][47][48]. The presence of a crystal was mainly due to its addition as an internal component for crystal-phase quantification purposes (Table 5).…”
Section: Steam-cured Strength Developmentmentioning
confidence: 99%
“…Figure 12 shows the results of the XRD measurements conducted on the raw FAs and paste powder from each mixture cured in ambient conditions for one day. The main crystal phases present in the FA37 sample were anatase (hereinafter, A), periclase (hereinafter, P), quartz (hereinafter, Q), gehlenite (hereinafter, G), and hatrurite (hereinafter, H), while those in the FA21 sample were A, Q, G, and P, and these were analyzed based on the findings of previous studies [44][45][46][47][48]. The presence of a crystal was mainly due to its addition as an internal component for crystal-phase quantification purposes (Table 5).…”
Section: Steam-cured Strength Developmentmentioning
confidence: 99%
“…Curing at higher temperatures, leads to a decrease in porosity in geopolymers [19]. Liu et al showed that curing at 40℃ demonstrated the best mechanical properties, with dense microstructures [20]. Yilmaz et al reported that curing times were more effective than curing temperatures in terms of porosity values, which decreased as the curing times increased [21].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the pore structure of the concrete was changed, and the volume of capillaries larger than 0.05 µm was reduced [26]. Moreover, GGBS plays an important role in filling voids between raw materials and reducing porosity so as to increase the compactness of concrete [27,28]. Adding GGBS decreases the permeability and increases the chemical stability of selfconsolidating concrete (SCC) due to the reaction of blast furnace slag with excess soluble calcium hydroxide [29,30], while ACBFS aggregates affect the flexural strength, but they improve other properties, such as the compressive strength and drying shrinkage [31].…”
Section: Introductionmentioning
confidence: 99%